PREPARATION OF HIGHLY ACTIVE Co-Mo/Al2O3 HDS CATALYSTS WITH CITRIC ACID ADDITION BY THE POST-TREATMENT METHOD - Nino Rinaldi (Indonesian Journal of Chemistry, 2010)
A study of the influence of citric acid (CA) addition by a post-treatment method during the preparation of a series of Mo/Al2O3 catalysts on the thiophene HDS activity was conducted. The Mo/Al2O3 catalysts were also prepared by a chemical vapor deposition (CVD) technique using Co(CO)3NO to introduce Co atom and characterized by means of NO adsorption, XRD, Mo K-edge EXAFS and XRF. With 8.7 wt% Mo, citric acid was not affected very much for the Co-Mo/Al2O3 catalysts. On the other hand, an outstanding result was shown that the HDS activity was drastically enhanced by 5 times up to Mo content around of 25 wt% Mo. It is suggested that the post treatment increased the dispersion of MoS2 particles, in particular at a high Mo loading. This was also supported by the amount of NO adsorption and amount of Co anchored by the CVD results, which enhanced as the increasing Mo loading up to 25 wt% Mo. Moreover, Mo-CA complex species were observed on the post-treatment method and CVD technique was one of advanced method to prepare Co-Mo-S phases selectively.